Oryza glaberrima Steud. - Ndjiondjop M.N.; Wambugu P.; Sangare J.R.; Dro T.; Kpeki B.; Gnikoua K. (Springer, 2018)
Oryza glaberrima is the African cultivated rice species, domesticated from its wild ancestor by farmers living in Inland Delta of Niger River. Several studies indicated that it has extremely narrow genetic diversity compared to both its wild progenitor, Oryza barthii and the Asian rice, Oryza sativa which can mainly be attributed to a severe domestication bottleneck. Despite its scarcity in farmer's field due to its low yield potential, high shattering and lodging susceptibility, O. glaberrima is of great value not only to Africa but also globally. Perhaps its greatest contribution to regional and global food security is as a source of genes, as it possesses resistance/tolerance to various biotic and abiotic stresses. It also has unique starch-related traits which give it good cooking and eating properties. Advances in DNA sequencing have provided useful genomic resources for African rice, key among them being whole genome sequences. Genomic tools are enabling greater understanding of the useful functional diversity found in this species. These advances have potential of addressing some of the undesirable attributes found in this species which have led to its continued replacement by Asian rice. Development of new generation of rice varieties for African farmers will therefore require the adoption of advanced molecular breeding tools as these will allow efficient utilization of the wealth and resilience found in African rice in rice improvement.